Listening to the voices of patients with cancer, their advocates and their nurses: A hermeneutic-phenomenological study of quality nursing care - Charalambous, Andreas; Papadopoulos, Irena Rena; Beadsmoore, Alan (My University, 2008)
This article presents the findings from a hermeneutic-phenomenological study looking at the meanings of “quality nursing care” through the experiences of patients with cancer, their advocates and their nurses. Twenty-five patients were interviewed from which fifteen also participated in two focus groups. Six patients' advocates participated in a focus group and twenty nurses were individually interviewed. The informants came from the three major hospitals in Cyprus which provide in-patient cancer care. Patients' advocates came from the two major cancer associations in Cyprus. Having analysed the data, seven major themes were identified: receiving care in easily accessible cancer care services, being cared for by nurses who effectively communicate with them and their families and provide emotional support, being empowered by nurses through information giving, being cared for by clinically competent nurses, nurses addressing their religious and spiritual needs, being cared for in a nursing environment which promotes shared decision-making, and patients being with and involving the family in the care. These findings stress the need to integrate these aspects in the care of patients with cancer. In doing so, nurses will need support and adequate training in order to acquire the relevant skills towards better caring for the patients.
Keywords: Quality nursing care; Patients with cancer; Hermeneutic phenomenology; Ricoeur; Interpretation theory